Shaping Immune Responses by Dysregulated Adipokines in Obesity - Enyu Rao; Bing Li; Yuwen Zhang (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2014)
Obesity is a major epidemic worldwide. According to the Centers for Disease Control and Prevention (CDC), about 34.9% of adults and 17% of children and adolescents are obese in the United States. The increasing prevalence of obesity poses a major threat to public health. Clinical and epidemiological data have established that obesity not only links to the development of diabetes, atherosclerosis and cardiovascular diseases, but also increases the risk of many types of cancer [1]. Although tremendous effort has been taken to investigate the pathogenesis of obesity and its associated diseases, the molecular mechanisms by which obesity negatively impacts on metabolic and immunologic homeostasisand increases the morbidity and mortality of many maladies remain largely unknown.